TAFSIR RUH AL-BAYAN KARYA ISMA’IL HAQI DAN PANDANGANNYA TENTANG TAFSIR DENGAN PENDEKATAN SUFI-ISHARI - Kusroni, Kusroni (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2019)
This paper discusses the existence of one interpretations approach that developed quite rapidly in the interpretation of Alquran, that is the Sufi approach or ishari. In the eighteenth century AD was born a scholar in the city of Aidos, Turkey, named Isma'il Haqi. This ulama was born and grew up in a Sufi environment and the family that adheres to the tarekat, therefore, he becomes a Sufi scholar and has competence in the field of Al-Qur'an Interpretation. The Book of Ruh al-Bayan Fi Tafsir al-Qur'an is magnum-opus in the field of interpretation. In this book he uses the Sufi-ishari approach in interpreting verses of Quran. In his view, the interpretation of ishari is the result of ma'rifat, if there is no element in it deviations from the Qur'an and al-Sunnah, and not based on the interests of desire when interpreting as what has done by some inner groups. .